Pembentukan Karakter Bagi Peserta Didik Sekolah Menengah Atas Dalam Pembelajaran Seni Tari Melalui Model Discovery Learning - Etik Riyaningsih; Maryono Maryono; Harini Harini (Teknodika, 2018)
Education as a conscious and planned effort in actualizing the study and learning atmosphere in developing the potential. Actualize education in the educational order to produce qualified human resources. Every human being has a character inherent in his daily behavior that is understood as ambitus. A person has a good character when their daily life has good habits. To grow character values and behaviors is not an easy task, it is necessary to apply the characters so that values are embedded and manifested in their daily behavioral actions. High School is one of the educational unit that implements the learning of art and culture that can shape the character of learners through the learning of dance. The research aims to describe the shaping of characters for high school students in the learning of dance through the Discovery Learning model. The research using a qualitative approach. Data sources such as informants, documents, places and events. Data collection techniques using observation, interview, documentation and recording. Data validity techniques using triangulation source and triangulation method. Data analysis techniques using interactive analysis model. The results showed that the learning of dance through the Discovery Learning model can form the character of the students. Can be shown at the stage in the model as follows: Stage of stimulus built an attitude of  responsibility; The stage of problem identifying formed the attitude of cooperation and responsibility; The stage of collecting data emerging honest and responsible; Stage data processing with the value of cooperation; Stage of verifying and concluding with an attitude of responsible